Nkx2.2-repressor activity is sufficient to specify α-cells and a small number of β-cells in the pancreatic islet - Doyle, Michelle J. (2007)
The homeodomain protein Nkx2.2 (Nkx2-2) is a key regulator of pancreatic islet cell specification in mice; Nkx2.2 is essential for the differentiation of all insulin-producing β-cells and of the majority of glucagon-producing α-cells, and, in its absence, these cell types are converted to a ghrelin cell fate. To understand the molecular functions of Nkx2.2 that regulate these early cell-fate decisions during pancreatic islet development, we created Nkx2.2-dominant-derivative transgenic mice. In the absence of endogenous Nkx2.2, the Nkx2.2–Engrailed-repressor derivative is sufficient to fully rescue glucagon-producing α-cells and to partially rescue insulin-producing β-cells. Interestingly, the insulin-positive cells that do form in the rescued mice do not express the mature β-cell markers MafA or Glut2 (Slc2a2), suggesting that additional activator functions of Nkx2.2 are required for β-cell maturation. To explore the mechanism by which Nkx2.2 functions as a repressor in the islet, we assessed the pancreatic expression of the Groucho co-repressors, Grg1, Grg2, Grg3 and Grg4 (Tle1-Tle4), which have been shown to interact with and modulate Nkx2.2 function. We determined that Grg3 is highly expressed in the embryonic pancreas in a pattern similar to Nkx2.2. Furthermore, we show that Grg3 physically interacts with Nkx2.2 through its TN domain. These studies suggest that Nkx2.2 functions predominantly as a transcriptional repressor during specification of endocrine cell types in the pancreas.